The The Role Of The Food Crops Sub Sector In The East Java Economy (Input – Output Approach) - Annisa Choiroh (Jurnal Ekuilibrium, 2020)
This study aim to analyze the forward and backward lingkages of the food crop sub-sector to other economic sectors in East Java to analyze the distribution power and degree of sensitivity of the food crop sub – sector to other economic sectors in East Java and to analyze the multiplier figurs in East Java. The method in this study uses descriptive quantitative research. The data analyzed are input – output data with 23 sectors classification. The results showed that the food crops sub-sectot had a low forward and backward lingakge value when compared to other sectors. The results of the sensitivity and distribution coefficiend indicate that the food crops sub-sector has a lower value compared to other sectors. Judging from the multiplier value shows that none of the contributions from the food crops sub sector has the highest contribution compared to other economic sectors in East Java Province.